(untitled) (Linguostylistic Studies, 2021)
The article deals with the analysis of four conversations about Lesya Ukrainka between the Primate of the Ukrainian Greek Catholic Church, His Beatitude Sviatoslav Shevchuk, and the writer Oksana Zabuzhko, attached to Lesya Ukrainka’s book “Apocrypha” and devoted to her attitudes to religion. The interlocutors explain the themes of Christology (images of Judas, Christ, the cult of martyrdom, sacrifice), Christianity and feminism, the idea of loneliness, which is one of the most important existential themes of modern culture, the role of the prophet in society, the issue of the Church and family, the topic of the lost Ukrainian paganism, etc. and they conclude that Lesya Ukrainka is an apologist for Christianity, but not Christianity as a system of doctrine, of abstract, logical formations, but Christianity as a “living communion with God”. Linguistic and stylistic features of the analysed text testify the emergence of a new genre in Ukrainian literature – intellectual dialogue, which is characterized by an extremely high level of scientificity (with a rich use of special narrow metalanguage) and modern linguistic means, including intertextuality (citations of the Holy Scriptures, of Church Fathers’ works, of prominent theologians, philosophers, famous modern figures, the use of expressions in different languages (Latin, English, German, Polish, etc.); diversity of vocabulary (Church Slavonic – colloquial vocabulary); application of surzhyk and slang elements in the normalized speech; the presence of spoken intonations; a combination of extreme seriousness with humour (sometimes irony), etc .